(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Assessing the tourism image of a place, provide an important diagnostic insight into how people see tourism in a destination, which is a very important marketing tool for planning, development and promotion of the tourism industry. The aim of this study is to access the image of tourism in Taraba state and to suggest measures that can improve and sustain a positive tourism image for the state. The study was taken at five sample tourist sites in which eight hundred (800) tourists were sample in the state using non proportional quota sampling technique. The study established that peace safety and security are prerequisite requirement for a positive destination image. The study confirmed that Taraba state is very rich in tourist attractions which if adequately planned developed promoted managed will make her one of the leading tourist destinations in Nigeria. However, the image of the state has rotated between positive when the state enjoyed peace, safety and security and negative during the incessant cycle of violent communal crisis that have befallen the state since 2002. To achieve a good attractive and sustainable tourism destination image of Taraba state the study made some recommendations to include religious political and ethnic tolerance and understanding as well as provision of adequate security for sustainable peace enthronement good tourism planning, development and promotion. Keywords: Destination, Image, Taraba State, Tourism, Perception